Analysis of the Distillation Column of a Catalytic Cracking Unit Using Fuzzy Input Information - Dinara Kozhakhmetova; Samal Kaliyeva; Laura Sugurova; Zharkynay Sugur; Ryszard Wójtowicz; Tursynkhan Zhylkybayev (Energies, 2024)
The aim of this work is to analyze and model the performance of the distillation column of a catalytic cracking plant using fuzzy initial information. A system of mathematical models of the studied columns was developed, and we discussed the issues of modeling the distillation column of a catalytic cracking plant operating in conditions of fuzzy initial information. The system of mathematical models of the studied columns was developed on the basis of statistical and fuzzy information. The mathematical models of columns K-1, K-2 and K-3 were identified with regression and fuzzy regression equations, i.e., combined models of the main columns of the catalytic cracking plant were constructed. The purpose of this study was to create an optimal control system for the distillation column of a catalytic cracking unit using a mathematical model of the process. The results obtained in this work can be helpful during the design, modernization and optimization of equipment and installations, especially those used in the chemical and petrochemical industries. They can be useful both from a scientific and practical point of view, and they are also significant in terms of environmental protection, economy and mechanical engineering.